Collaborative Governance Oversight in Corruption Prevention Efforts in Indonesia - Ucok Abdulrauf Damenta; Kumba Digdowiseiso (Journal of Governance, 2023)
Prevention of corruption in Indonesia is not an easy task. Corruption has been a serious problem in Indonesia for decades. To overcome this problem, joint efforts from the government, private sector and the community are needed. One way to overcome this problem is to use collaborative governance which is the aim of this research. In the context of preventing corruption, collaborative governance has an important role in maintaining accountability and transparency in public financial management. This research is descriptive qualitative research with data sources derived from a literature review. This article discusses the meaning of collaborative governance and oversight of corruption prevention, the role and function of collaborative governance in preventing corruption, the determining factors for the success of collaborative governance in preventing corruption, and the implementation of collaborative governance in preventing corruption in Indonesia. The implication of this research is that efforts to prevent corruption in Indonesia are a joint responsibility of the government, private sector and society because good collaboration between the three can strengthen the system of oversight and control of corrupt practices.